Influence of heterogeneous individual growth on male freshwater prawn Macrobrachium rosenbergii de man for sustainable monosex culture - Banu, Mst. Rubia (2014)
Males of freshwater prawn Macrobrachium rosenbergii grow faster and larger than females. There has been a significant problem which appeared in all-male culture, namely their heterogeneous individual growth (HIG) pattern. Three different morphotypes of male prawn are found at harvest, namely blue-clawed male (BC), orange clawed male (OC) and small male (SM). Sometimes as much as 50% of harvested prawns remain undersized SM, which is one of the major impediments in freshwater prawn farming and its profitability. The purpose of this study was to investigate the effects and methods to minimize HIG occurrence in male prawns. This study was conducted at the hatchery unit at Universiti Putra Malaysia. Juveniles of M. rosenbergii collected from Negeri Sembilan were used for all experiments. In the first experiment, three stocking densities of all-male prawns viz., 20, 30 and 40 juvenile m-2 were carried out in triplicates. After 4 months of culture, BC, OC and SM were counted from each treatment. It was found that the highest survival rate combined with good yield performance was from 20 m-2 stocking density with 21% BC, 62.5% OC and 16.5% SM respectively. In the second experiment, male juveniles M. rosenbergii were segregated into BC, OC and SM, and cultured in isolation in fiberglass tanks at 5 m-2 for 80 days. SM population had the highest growth rate with three times growth increment, followed by the OC and BC population. The SM population had 100% survival rate with an average specific growth rate (SGR) of 1.22 % wt/day (average harvested individual weight 29 g); the OC and BC population had 72% survival rate with an average SGR of 1.01 and 0.43 (42 g and 30 g) respectively. The wet weight gain of prawns was significantly greater for OC males (23.87 g) compared with SM (19.57 g) and BC males (6.31 g). Impacts of isolated culture on population structures were much more pronounced in the SM population than in the other morph cohorts. In the third experiment, groups of small male (SM) M. rosenbergii juveniles were subjected to two treatments: bilateral eyestalk ablation and unablated/controls. Variation in individual growth rate of bilaterally ablated prawns was higher when compared with unablated prawns. In particular, the SGR of bilaterally ablated prawns (1.90%) was significantly higher than unablated prawns (1.15%). The absolute weight of ablated prawns was twice that of the controls. The growth trend of SM prawns at the end of the experiment was significantly increased compared with controls until the end of the experiment. These results suggested the potency of bilateral eyestalk ablation in enhancing growth rates might be limited due to high mortalities of the ablated prawns. In the last experiment, male juveniles of M. rosenbergii were subjected cold shock and hormonal treatments. Individual growth of male juveniles was homogenous for the cold shock treated group (CLS) but was heterogeneous for the 17α methyl testosterone hormone treated (MH) and the control (CO) groups. The morphotypes of male prawns were significantly different in all treatments. It was observed 59% of BC males with small blue claws in the CLS treatment while 45 and 30 % BC males with large blue claws in MH and CO treatments, respectively. Average growth of prawn was not significantly different in all treatments including controls but the size of blue claw was smaller in the CLS treatment compared to others.